Formation of papaya seedlings using dairy wastewater in the substrate - Santos, Verônica Andrade dos; Ramos, José Darlan; Oliveira, Marcelo Caetano de; Magalhães, Deniete Soares; Fagundes, Miriã Cristina Pereira; Luiz, Paulo Henrique Dionizio (Revista de Ciências Agroveterinárias, 2018)
The state of Minas Gerais is a major producer of waste from the manufacture of dairy products, whose potential reuse, besides serving as a source of nutrients, can prevent the pollution of water sources and soil. The aim of this study was to analyze the development of papaya seedlings with use of dairy-production wastewater, considering nutritional and hydric needs in their formation. The 5 x 2 factorial structure under a randomized block design, with the factors: concentration of dairy wastewater (0, 25, 50, 75 and 100%) and two types of substrates Bioplant® and a mixture of soil, sand and manure, at a ratio 2:1:1, with four replications of eight plants per plot. After 60 days, the following characteristics were evaluated: length of shoot and root (cm), number of leaves, stem diameter (mm), dry matter of the aerial part and root system (g) and analysis of macro and micronutrient present. The highest development of papaya seedlings occurred with the application of dairy-production wastewater at a concentration of 100% when used with substrate constituted by soil, sand and manure, meeting hydric and nutritional demand in the initial phase of papaya seedlings.